Sports Science and Human Health - Different Approaches 2020
DOI: 10.5772/intechopen.91356
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Future of Wearable Technology in Human Motor-Skill Learning and Optimization

Abstract: Learning how to move is a challenging task. Even the most basic motor skill of walking requires years to develop and can quickly deteriorate due to aging and sedentary lifestyles. More specialized skills such as ballet and acrobatic kicks in soccer require "talent" and years of extensive practice to fully master. These practices can easily cause injuries if conducted improperly. 3D motion capture technologies are currently the best way to acquire human motor skill in biomechanical feedback training. Owing to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Marne et al (2016) demonstrated that future wearables would work with greater efficiency, accuracy, flexibility and enhanced privacy measures in order to carry out complex tasks. Previous researches have examined the applications of wearable technology across various fields: healthcare (Talukdar et al, 2019), forensic and clinical sciences (Ferreira et al, 2019), sports (Aroganam et al, 2019), biofeedback human skill-training (Shan, 2020), smart textiles (Mokhtari et al, 2020), infotainment (Sinnapolu & Alawneh, 2020), military and AR/VR industries (Vermetten et al, 2020), etc.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Marne et al (2016) demonstrated that future wearables would work with greater efficiency, accuracy, flexibility and enhanced privacy measures in order to carry out complex tasks. Previous researches have examined the applications of wearable technology across various fields: healthcare (Talukdar et al, 2019), forensic and clinical sciences (Ferreira et al, 2019), sports (Aroganam et al, 2019), biofeedback human skill-training (Shan, 2020), smart textiles (Mokhtari et al, 2020), infotainment (Sinnapolu & Alawneh, 2020), military and AR/VR industries (Vermetten et al, 2020), etc.…”
Section: Review Of Literaturementioning
confidence: 99%